Modelling Antarctic ice shelf basal melt patterns using the one-layer Antarctic model for dynamical downscaling of ice–ocean exchanges (LADDIE v1.0) - E. Lambert; A. Jüling; R. S. W. van de Wal; R. S. W. van de Wal; P. R. Holland (The Cryosphere, 2023)
A major source of uncertainty in future sea level projections is the ocean-driven basal melt of Antarctic ice shelves. While ice sheet models require a kilometre-scale resolution to realistically resolve ice shelf stability and grounding line migration, global or regional 3D ocean models are computationally too expensive to produce basal melt forcing fields at this resolution on long timescales. To bridge this resolution gap, we introduce the 2D numerical model LADDIE (one-layer Antarctic model for dynamical downscaling of ice–ocean exchanges), which allows for the computationally efficient modelling of detailed basal melt fields. The model is open source and can be applied easily to different geometries or different ocean forcings. The aim of this study is threefold: to introduce the model to the community, to demonstrate its application and performance in two use cases, and to describe and interpret new basal melt patterns simulated by this model. The two use cases are the small Crosson–Dotson Ice Shelf in the warm Amundsen Sea region and the large Filchner–Ronne Ice Shelf in the cold Weddell Sea. At ice-shelf-wide scales, LADDIE reproduces observed patterns of basal melting and freezing in warm and cold environments without the need to re-tune parameters for individual ice shelves. At scales of 0.5–5 km, which are typically unresolved by 3D ocean models and poorly constrained by observations, LADDIE produces plausible basal melt patterns. Most significantly, the simulated basal melt patterns are physically consistent with the applied ice shelf topography. These patterns are governed by the topographic steering and Coriolis deflection of meltwater flows, two processes that are poorly represented in basal melt parameterisations. The kilometre-scale melt patterns simulated by LADDIE include enhanced melt rates in grounding zones and basal channels and enhanced melt or freezing in shear margins. As these regions are critical for ice shelf stability, we conclude that LADDIE can provide detailed basal melt patterns at the essential resolution that ice sheet models require. The physical consistency between the applied geometry and the simulated basal melt fields indicates that LADDIE can play a valuable role in the development of coupled ice–ocean modelling.